Wilsonova choroba - Brůha, R; Marecek, Z; Martásek, P; Nevsímalová, S; Petrtýl, J; Urbánek, P; Kalistová, H; Pospísilová, L (Casopis lekaru ceskych, 2009)
Wilson's disease is an inherited disorder leading to accumulation of copper in tissues, mainly in the liver and brain. Genetic defect is in the gene coding ATPase type P (ATP7B). The inheritance is autosomal recessive. Up to now, more then 500 mutations causing Wilson's disease were described. The most frequent mutation in Central Europe is mutation H1069Q. The manifestation of Wilson's disease is usually hepatic or neurologic. Hepatic form is manifested by acute or chronic hepatitis, steatosis or cirrhosis. Neurologic involvement is manifested usually after 20 year of age by motor disturbances (tremor, disturbed speech, problems with writing), which could progress into severe extrapyramidal syndrome with tremor, rigidity, dysartria, dysfagia and muscle contracture. Diagnosis is based on clinical and laboratory examinations (neurologic symptoms, liver disease, low serum ceruloplasmin levels, elevated free copper concentration in serum, high urine copper excretion, and presence of Kayser-Fleischer rings). Confirmation of diagnosis is done by hepatic copper concentration in liver biopsy or by genetic examination. Untreated disease leads to the death of a patient. Treatment is based on chelating agents decreasing the copper content by excretion into urine (D-penicillamine, trientine) or on agents preventing absorption of copper from food (zinc, ammonium-tetrahiomolybdene). Patients with asymptomatic Wilson's disease have to be treated as well. In Czech Republic either penicillamine or zinc are used. Liver transplantation is indicated in patients with fulminant liver failure or decompensated cirrhosis. Screening in families of affected patients (all siblings) is obvious.
Keywords: lidé; hepatolentikulární degenerace; Hepatolenticular Degeneration; Prognosis; Humans; prognóza